2019
DOI: 10.3390/app9081593
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Bragg Reflectors for GaN-Based Vertical-Cavity Surface-Emitting Lasers

Abstract: A distributed Bragg reflector (DBR) is a key building block in the formation of semiconductor microcavities and vertical cavity surface emitting lasers (VCSELs). The success in epitaxial GaAs DBR mirrors paved the way for the ubiquitous deployment of III-V VCSELs in communication and mobile applications. However, a similar development of GaN-based blue VCSELs has been hindered by challenges in preparing DBRs that are mass producible. In this article, we provide a review of the history and current status of for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 123 publications
(147 reference statements)
1
44
0
1
Order By: Relevance
“… 2 The VCSEL market will be further expanded when visible-emitting GaN-based VCSELs are commercialized. This will soon be a reality based on the recent immense improvement in performance 3 8 enabled by advances in thermal management, 3 , 6 , 9 optical confinement, 5 , 10 , 11 mirror reflectivity, 8 , 10 , 12 and electrical injection. 7 , 13 Part of these advances may also boost the development of ultraviolet (UV) AlGaN-based VCSELs, sources with a higher brightness than LEDs.…”
mentioning
confidence: 99%
“… 2 The VCSEL market will be further expanded when visible-emitting GaN-based VCSELs are commercialized. This will soon be a reality based on the recent immense improvement in performance 3 8 enabled by advances in thermal management, 3 , 6 , 9 optical confinement, 5 , 10 , 11 mirror reflectivity, 8 , 10 , 12 and electrical injection. 7 , 13 Part of these advances may also boost the development of ultraviolet (UV) AlGaN-based VCSELs, sources with a higher brightness than LEDs.…”
mentioning
confidence: 99%
“…This additional constraint demonstrates the potential of the technique to generate solutions for the designer under multi-constrained conditions and the same process may be flexibly applied to achieve other desired goals. The stopband width is defined for R>99%, typically required for low threshold VCSEL mirrors [22], [34]. We define the fabrication tolerance for the center wavelength (500nm and 1.55μm) as the maximum continuous stretch of a given grating parameter that yields reflectivity values greater than 99% at the center wavelength.…”
Section: Optimization Techniquementioning
confidence: 99%
“…Broadband SWG reflectors have been proposed for III-Nitride VCSELs [15]- [17]. The commercial success of III-Nitride VCSELs has long been impeded by difficulties with growing high-quality distributed Bragg reflectors (DBRs) due to challenges with high lattice mismatch, low index contrast and low p-type doping issues associated with III-Nitride alloys of choice [18]- [22]. SWGs can be designed to simultaneously satisfy high peak reflectivity (R>99%) and a wide stopband necessary for fabrication tolerance of the VCSELs and thus be an effective alternative for III-Nitride DBRs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported GaN‐based resonant cavity devices using different approaches (e.g., dual dielectrics, epitaxy, hybrid cavity structures, etc.) 21–25. However, due to limitations in the epitaxy and/or device fabrication, further developments are needed.…”
Section: Introductionmentioning
confidence: 99%